Cross-Comparative Study of Millennial Investment Interest: The Roles of Herding Behavior, Risk Perception, and Financial Literacy - Yulia Citra Pesona; Nurul Hidayah (Transpublika Publisher, 2025)
The increasing number of capital market participants in Indonesia is displaying a promising pattern, particularly with the active involvement of millennials. Nonetheless, data from the Indonesian Central Securities Depository (KSEI) highlights a notable difference in the amount of Sharia-compliant and traditional investors in the country. A study was conducted to compare the investment preferences of millennials in sharia-compliant and conventional investment options. The study focused on analyzing herding behavior, risk perception, and financial knowledge. The research employed a quantitative approach utilizing the Partial Least Squares (PLS) based Structural Equation Model (SEM) analysis technique. Findings from the data analysis suggest that herding behavior does not strongly influence the investment preferences of millennial investors, whether they are interested in sharia-compliant or conventional investments. Nonetheless, the way in which risks are viewed and understanding of financial matters do impact the inclination of millennial investors towards both sharia and conventional investments in a positive and notable manner. This suggests that many millennial investors possess a solid grasp of financial concepts and are mindful when making investment choices. The findings of this research can be utilized by governmental bodies for research purposes in order to boost the interest of the youth in investments, particularly in sharia-compliant investments, and to promote initiatives that enhance knowledge and understanding of investment options, both sharia-compliant and conventional.